Development of Niacinamide/Ferulic Acid-Loaded Multiple Emulsion and Its In Vitro/In Vivo Investigation as a Cosmeceutical Product. (17th March 2022) - Huma, Sidra; Khan, Haji Muhammad Shoaib; Ijaz, Shakeel; Sarfraz, Muhammad; Zaka, Hafiz Saqib; Ahmad, Aousaf
Abstract : Objective . Multiple emulsions have the ability to incorporate both lipophilic and hydrophilic actives in the same preparation and facilitate permeation of active ingredients through skin. The current study was aimed at formulating niacinamide/ferulic acid-loaded stable multiple emulsion (MNF) and its in vitro / in vivo characterization as a cosmeceutical product. Methods . Both the compounds were evaluated for their radical scavenging potential by the DPPH method and FTIR analysis. Then, placebo and active formulations were prepared using a double emulsification method and were investigated for stability testing (changes in color, odor, and liquefaction on centrifugation, pH, and globule size) for a period of three months. Afterwards, MNF was investigated for in vitro sun protection factor, rheological studies, entrapment efficiency, zeta potential, zeta size, and ex vivo permeation. Moreover, after ensuring the hypoallergenicity and safety, it was also checked for its cosmeceutical effects on human skin using noninvasive biophysical probes in comparison with placebo. Results . Results demonstrated that MNF showed a non-Newtonian behavior rheologically and both MNF and placebo were stable at different storage conditions. Entrapment efficiency, zeta potential, and zeta size were 93.3%, -5.88 mV, and 0.173 μ m, respectively. Moreover, melanin, sebum, and skin erythema were significantly reduced while skin elasticity and hydration were improved. Conclusion . It is evident that niacinamide and ferulic acid can be successfully incorporated in a stable multiple emulsion which has potent cosmeceutical effects on human skin.